Complex thermal energy conversion systems for efficient use of locally available biomass. (1st September 2016) - Kalina, Jacek
Abstract: This paper is focused on a theoretical study in search for new technological solutions in the field of electricity generation from biomass in small-scale distributed cogeneration systems. The purpose of this work is to draw readers' attention to possibilities of design complex multi-component hybrid and combined technological structures of energy conversion plants for effective use of locally available biomass resources. As an example, there is presented analysis of cogeneration system that consists of micro-turbine, high temperature fuel cell, inverted Bryton cycle module and biomass gasification island. The project assumes supporting use of natural gas and cooperation of the plant with a low-temperature district heating network. Thermodynamic parameters, energy conversion effectiveness and economic performance are examined. Results show relatively high energy conversion performance and on the other hand weak financial indices of investment projects at the current level of energy prices. It is however possible under certain conditions to define an optimistic business model that leads to a feasible project. Highlights: Concept of biomass energy conversion plant is proposed and theoretically analysed. MCFC type fuel cell is fuelled with biomass gasification gas. Natural gas fired microturbine is considered as a source of continuous power. Inverted Bryton Cycle is considered for utilisation of high temperature exhaust gas.